(untitled) - Scoville, John W. (New York, 1942)
There are 43 T. N. E. C. monographs, plus two supplement monographs. Some of them represent studies made by the economic staff of the T. N. E. C., which also requested various participating goverment agencies to submit reports upon designated economic subjects.
Keywords: Investigation of concentration of economic power,Điều tra tập trung quyền lực kinh tế